The influence of microstructures of AM-316L stainless steel on mechanical properties - Chen, Kwok Fong (Nanyang Technological University, 2020)
Additive Manufacturing (AM) is a widely employed method to fabricate small to medium lot sizes of macro-components. In lieu of the increasing appeal for miniaturization, the focus is directed towards manufacturing micro and nanofeatures via AM. Selective Laser Melting (SLM) and Direct Energy Deposition (DED) are two of the most common AM techniques to fabricate metal components. This project aims to understand the influence of the microstructure of the fabricated samples on its mechanical properties. The manufactured part quality was analyzed for its defects and microstructure. A correlation between the microstructure and mechanical properties like tensile strength, yield strength and elongation were observed through machine learning algorithms like support vector machines. Microstructures of the samples were crucial in the understanding of any hidden correlations, which differ significantly according to the process conditions. The findings from this research will greatly speed up the process of characterizing fabricated samples in the future.